An Islamic Economic Perspective About Sources of Public Finance Revenue in Indonesia Based on Abu Ubaid’s and Ad-Dawudi‘s Thought - Baitul Hamdi; Tika Widiastuti (AFEBI Islamic Finance and Economic Review, 2021)
This paper discusses sources of Islamic public finance income based on the ideas of Abu Ubaid and Ad-Dawudi in the Al-Amwal book and makes them relevant to sources of income from Indonesian public finances. The writing uses a qualitative method with a literature study approach to analyze the thoughts of Abu Ubaid and Ad-Dawud. The results showed that the sources of public financial income according to Abu Ubaid are zakat, fa'I, and khumus. While according to Ad-Dawudi in the book Al-Amwal, the source of state income is divided into periodic income (jizyah and kharaj and usyur) non-income periodic (ghanimah, fa'I, and zakat). In general, it has relevance to public sources of finance in Indonesia, it's just that the system or amount is different. Kharaj, fai, usyur, khumus in the form of mining taxes, jizyah in the form of visas, ghanimah there are differences of opinion that can be equated with confiscated goods from the state due to violating the law while other opinions say they are irrelevant because they support war actions to acquire wealth, lastly, Zakat is still practiced in Indonesia and managed by BAZNAS and LAZ